Research Implementation of the Milkfish Feed Development from the Edible Mushrooms for a Digital-Based Module in Biotechnology Concept for High School Students - Fauziyah, Mila; Rahman KN, Aditya; Khastini, Rida Oktorida (Jurnal Penelitian dan Pembelajaran IPA, 2023)
This study aimed to analyze the results of research on the content of edible mushrooms as milkfish feed to be implied as a digital module, a learning source for biotechnology concepts for high school students. The study was carried out through stages: identifying the problems in biotechnology concepts learning activities in four state senior high schools in Banten Province, identifying research methods and products through experiments, choosing and adapting research findings as the learning source content, and applying and developing research findings as learning. An interview grid and questionnaire were used to collect the data, and a qualitative analysis was used to interpret the questionnaires' results. The research results were in the form of a digital-based module in biotechnology concepts for high school students. The module contains activities that create student interest and motivation and help students master the concepts. In addition, the module's content was a research finding on the milkfish feed development from the edible mushrooms in the form of process and product. It can be concluded that a digital module on biotechnology concepts has been developed and can be used as a learning source for high school student.